FAS mediates apoptosis, inflammation, and treatment of pathogen infection - Hu, Liying; Lu, Juane; Fan, Hongfei; Niu, Changcheng; Han, Yanping; Caiyin, Qinggele; Wu, Hao; Qiao, Jianjun (Frontiers in Cellular and Infection Microbiology, 2025)
The FAS cell surface death receptor, a member of the tumor necrosis factor receptor family, activates both apoptotic and non-apoptotic signaling upon interaction with its ligand FASL. It is critical in cell migration, invasion, immune responses, and carcinogenesis. Pathogen infection can influence host cells’ behavior by modulating the FAS/FASL pathway, thereby influencing disease progression. Understanding the role of FAS signaling in the context of pathogen interactions is therefore crucial. This review examines FAS-mediated apoptotic and non-apoptotic signaling pathways, with particular emphasis on the mechanisms of apoptosis and inflammation induced by bacterial and viral infections. Additionally, it highlights therapeutic strategies, including drug, cytokine, antibody, and FASL recombinant protein therapies, providing new directions for treating pathogenic infections and cancers, as well as insights into developing novel therapeutic approaches.